Reducing agents inhibit rhinovirus-induced up-regulation of the rhinovirus receptor intercellular adhesion molecule-1 (ICAM-1) in respiratory epithelial cells - Papi, A.; Papadopoulos, N. G.; Stanciu, L. A.; Bellettato, C. M.; Pinamonti, S.; Degitz, K.; Holgate, S. T.; Johnston, S. L. (FASEB J, 2002)
Rhinoviruses are the major cause of common colds and of asthma exacerbations. Intercellular adhesion molecule-1 (ICAM-1) has a central role in airway inflammation and is the receptor for 90% of rhinoviruses. Rhinovirus infection of airway epithelium induces ICAM-1. Because redox state is directly implicated in inflammatory responses via molecular signaling mechanisms, here we studied the effects of reducing agents on rhinovirus-induced ICAM-1 expression, mRNA up-regulation, promoter activation, and nuclear factor activation. To investigate the effects of rhinovirus infection on the intracellular redox balance, we also studied whether rhinovirus infection triggers the production of reactive oxygen species. We found that reduced (GSH) but not oxidized (GSSG) glutathione (1-100 microM) inhibited in a dose-dependent manner rhinovirus-induced ICAM-1 up-regulation and mRNA induction in primary bronchial and A549 respiratory epithelial cells. GSH but not GSSG also inhibited rhinovirus-induced ICAM-1 promoter activation and rhinovirus-induced NF-kB activation. In parallel, we found that rhinovirus infection induced a rapid increase of intracellular superoxide anion that was maximal at the time of NF-kB activation. This oxidant generation was completely inhibited by GSH. We conclude that redox-mediated intracellular pathways represent an important target for the therapeutic control of rhinovirus-induced diseases.
Keywords: Animals Cell Line Cells; Biological NF-kappa B Promoter Regions; Cultured Dose-Response Relationship; Drug Glutathione Intercellular Adhesion Molecule-1 Models; Genetic RNA; Messenger Receptors; Virus Reducing Agents Respiratory Mucosa Rhinovirus Superoxides Transcriptional Activation Up-Regulation